(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
Protease enzymes are ubiquitous in nature and usually found in all living organisms. The present study was conducted for screening bacteria with the ability to produce extracellular proteases. Attempts were made to isolate protease producing bacterial strains from soil samples of tannery wastes from Hazaribag, Bangladesh and subsequent partial characterization was performed. A number of biochemical assays was performed for presumptive identification of the bacteria. Subsequent molecular identification of bacterial isolates was performed using 16S rRNA sequence analysis, which revealed that the isolated bacterium R82 to be Bacillus subtilis. The protease enzyme activity was determined 60.50 U/mL. Further characterization showed that the enzyme produced from the bacteria was extracellular and alkaline protease in nature. The optimum reaction incubation time, pH and temperature were found to be 30 min, 8.0 and 50°C, respectively. Bacterial culture supernatant was used to carry out dehairing of leather (2ʹʹ×2ʹʹ), which was achieved in 24 h. The results showed that isolated bacterial strain could be employed for strain improvement towards commercial production of protease with a promise for dehairing in leather processing industries. Jahangirnagar University J. Biol. Sci. 7(1): 23-34, 2018 (June)